Answer:
x= -6
Step-by-step explanation:
y=4x-6
y=5x, so where ever you see y, put 5x there.
hence, 5x=4x-6
5x-4x=-6
x= -6
Answer:
Vertex form
y = -4(x + 3)^2 + 10
Standard form;
y = -4x^2-24x - 26
Step-by-step explanation:
Mathematically, we have the vertex form as
y = a(x-h)^2 + k
(h,k) represents the vertex
We have h as -3 and k as 10
y = a(x+3)^2 + 10
To get a, we substitute any of the points
Let us use (-1,-6)
-6 = a(-1+3)^2 + 10
-6-10 = 4a
4a = -16
a = -16/4
a = -4
So we have the equation as;
y = -4(x+3)^2 + 10
For the standard form;
We expand the vertex form;
y = -4(x + 3)(x + 3) + 10
y = -4(x^2 + 6x + 9) + 10
y = -4x^2 - 24x -36 + 10
y = -4x^2 -24x -26
Answer:
y =
x + 7
Step-by-step explanation:
the equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b ) a point on the line
y - 8 = -
(x + 5) ← is in point- slope form
with m = - ![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
given a line with slope m then the slope of a line perpendicular to it is
= -
= -
= ![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
the equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept ) , then
y =
x + c ← is the partial equation
to find c substitute (- 6, - 2 ) into the partial equation
- 2 = - 9 + c ⇒ c = - 2 + 9 = 7
y =
x + 7 ← equation of line K
Answer:
2(5+2)
Step-by-step explanation:
The greatest common factor would be 7. So now 35/7 is 5 and 14/7 is 2. Now put it in distributive property! GCF on the outside and the new numbers we just got in the inside. There's your answer! Have a great day! :)
Answer:
5 + 14 and 12 + 7
Step-by-step explanation: